Drug-resistant tuberculosis in war and complex emergencies: jeopardising progress towards TB elimination and antimicrobial resistance control – a scoping review and perspective - Monedero Recuero, Ignacio; Wei, Xiaolin; Jouberton, Fabienne; Duarte, Raquel; Rodríguez Ortega, María; T Santiago, Mary Rosary; Oyedokun Adekunle, Adekola; Daru, Paul; Felker, Irina; Conradie, Francesca; Isani, Afshan K; Chiang, Chen Yuan; et al. (My University, 2026)
Introducción: Cerca de 300 millones de personas requieren asistencia humanitaria debido a conflictos y emergencias complejas. Estos contextos interrumpen los sistemas sanitarios y dificultan la atención de la tuberculosis (TB), especialmente la tuberculosis farmacorresistente (TB-DR). Métodos: Se realizó una revisión exploratoria que incluyó literatura científica y gris, así como consultas con agencias implementadoras, para analizar experiencias globales en la provisión de atención a TB-DR en emergencias complejas. Resultados: Se identificaron 16 artículos revisados por pares y 11 informes. Los países en guerra presentan múltiples factores de riesgo para amplificar la resistencia. Las tasas de notificación son inferiores al 20% de los casos estimados, aunque las tasas de éxito terapéutico entre los diagnosticados son comparables al promedio mundial. Conclusión: La guerra altera significativamente la dinámica de la TB-DR y amenaza los avances hacia su eliminación.

Introduction: Nearly 300 million people globally require humanitarian assistance, primarily due to conflicts and complex emergencies (CE). Modern conflicts are increasingly prolonged, deadly and frequent, severely disrupting health systems and hindering the provision of quality tuberculosis (TB) care. Managing drug-resistant TB (DR-TB) in these settings is particularly challenging. Methods: A scoping review, including grey literature and consultation with implementing agencies, was conducted to analyse published experiences worldwide in delivering DR-TB care in CE. Results: The review included 16 peer-reviewed articles and 11 reports. Countries affected by war exhibit multiple risk factors for amplifying TB resistance. Diagnostic access is limited, with notification rates below 20% of estimated cases. Conclusions: War significantly alters DR-TB dynamics, threatening progress towards TB elimination and exacerbating antimicrobial resistance globally.
Artículos en revistas